Assessment of membrane photobioreactor (MPBR) performance parameters and operating conditions. (1st July 2018) - Luo, Yunlong; Le-Clech, Pierre; Henderson, Rita K.
Abstract: Membrane photobioreactor (MPBR) technology is an emerging algae-based wastewater treatment system. Given the limitations due to the general use of conventional analytical approaches in previous research, this study aims to provide a more comprehensive assessment of MPBR performance through advanced characterisation techniques. New performance parameters are also proposed, encompassing five important aspects of MPBR system efficiency (i.e. biomass concentration, composition, production, nutrient uptake and harvesting potential). Under initial standard operating conditions, performance parameters, such as cell count/MLSS ratio, cell viability, proportion of bacteria and biomass yield coefficient, were found to offer new insights into the operation of MPBR. These parameters were then used, for the first time, to systematically investigate MPBRs operated under different hydraulic retention times (HRTs) and solids retention times (SRTs). Applying shorter HRT and SRT was observed to increase cell viability and productivity (up to 0.25 × 10 7  cells/mL·d), as anticipated due to the higher nutrient loading. It was noted that the faster growing algal cells featured lower requirement for nutrients. On the other hand, extending HRT and SRT resulted in a more heterogeneous culture (lower cell count/MLSS ratio and higher proportion of bacteria), achieving a higher degree of autoflocculation and greater NO3 -N and PO4 -P removals of up to 79% and 78% respectively. The results demonstrate the trade-off between applying different HRTs and SRTs and the importance of fully characterising system performance to critically assess the advantages and limitations of chosen operating conditions. Graphical abstract: Image 1 Highlights: New parameters are proposed to better assess MPBR performance. Flow cytometry provides new insight into biomass characterisation. Advantages and limitations were identified for different operating conditions.